Yasmin Politeness Strategies Related to Power Relation in Ayu Utami’s Maya - Darta, Deta Maria Sri; Widiningrum, Rindang; Suryaningsih, Ervin; Hartawan, Ni Putu Zefanya Putri Gracia; Wahyuni, Herlin Tri (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. The main character, Yasmin, in the novel Maya was described as a strong and independent woman. Her relationship with other characters in the novel was the main focus of this research in terms of the power relation between Yasmin and other characters. This study aimed to find out Yasmin’s traits (in addition to the existing traits analyzed) through the analysis of politeness strategies used by Yasmin in her relationship with other characters. Qualitative method was used in which data analyzed were utterances. The utterances were analyzed based on the power relation between speaker and hearer as well as the politeness strategies used. The discussion showed that Yasmin used positive politeness more than other strategies and put herself in the position of holding the power in her relationship with other characters. Thus, Yasmin can be considered as a person who is confident as well as flexible. Keywords: Politeness Strategies, Character, Power Relation